Sentence Repetition in Farsi-English Bilingual Children - Mariam Komeili; Theodoros Marinis; Parvaneh Tavakoli; Yalda Kazemi (Journal of the European Second Language Association, 2020)
The current study aimed to create an assessment that can be used in the future to measure the language abilities of Farsi-speaking children in a clinical setting. A Farsi sentence-repetition task was created that included structures organised into three levels of complexity from least to most complex. Twenty typically developing Farsi-English bilingual children between the ages of 6;3–11;6 were recruited from Farsi schools in Toronto, Canada. Significant differences on the participants’ performance among the three levels were found with the lowest performance in the most complex sentences and the highest performance in the least complex ones. Specific structures appeared to be more challenging than others within each level of complexity. The children’s decreasing performance with increasing complexity and the evidence that specific structures are challenging within each level make the Farsi sentence repetition task a promising tool for assessing the language skills of Farsi-English speaking children.